Pengaruh Lingkungan Kerja Terhadap Kinerja Pegawai Pada Dinas Pendidikan Kebudayaan Pemuda dan Olahraga - Atmanda Mokodompit; Radia Hafid; Melizubaida Mahmud; Raflin Hinelo; Ardiansyah Ardiansyah; Yulianti Toralawe (Journal of Economic and Business Education, 2023)
It employed a quantitative approach with a descriptive research method. The population in this research were empoloyees at the Education, Culture, Youth and Sports Office of Gorontalo Province, with a total population of 335 respondents and the research samples were 40 employees. At the same time, the data collection technique used questionnaires, while the data analysis was done through simple linear regression analysis. The correlation analysis results depicted that there was an effect of work enviironment on employees’ performance at the Education, Culture, Youth and Sports Office of Gorontalo Province. This was proven by the correlation coefficient value of 0.758. The calculation of the coefficient of determination obtained an R-square value of 0.575, which meant that 57,5% of the variability of employees’ performance at the Education, Culture, Youth and Sports Office of Gorontalo Province could be explained by the work environment , The remaining 42.5% was affected by other variables that were not examined in this research.